Humanized medical assistance in undergraduate degree: an integrative literature review (Research, Society and Development, 2022)
Medical practice is currently based mostly on science and technology, scientific research and discoveries. When it comes to humanization, especially during graduation, the student ends up distancing himself, preferring to improve in subjects that aim only at practical training contents. This article aimed to highlight the concept of humanized care in medical practice described in national and international literature. An integrative review was carried out in three databases, with the descriptors “Humanization of Assistance”, “Student Medical” and “Medicine”, making a final sample of 13 articles. The concept of humanization is related to biopsychosocial aspects and is fundamental for the construction of an effective clinical practice. The exercise of humanization during the medical course is hardly seen throughout academic training as it should essentially be experienced through mandatory subjects. In addition, disciplines aimed at the development of a reflection on the individual as a whole is the great challenge in a century characterized by great discoveries and high technological development. Scientific production demonstrates that subjects focused on the theme of Humanization are considered less relevant for medical students, despite the evidence of their benefits for a more sensitive and complete training. Medical education needs strategies that can link the humanities to the biological areas. The challenge is to rescue the concept of humanization of care in a scenario characterized by technology and protocols that aim at the health-disease process, distancing itself from the human, which truly matters.